Associations among plasma metabolite levels and short-term exposure to PM2.5 and ozone in a cardiac catheterization cohort. (December 2016) - Breitner, Susanne; Schneider, Alexandra; Devlin, Robert B; Ward-Caviness, Cavin K; Diaz-Sanchez, David; Neas, Lucas M; Cascio, Wayne E; Peters, Annette; Hauser, Elizabeth R; Shah, Svati H; Kraus, William E
Abstract: Rationale: Exposure to ambient particulate matter (PM) and ozone has been associated with cardiovascular disease (CVD). However, the mechanisms linking PM and ozone exposure to CVD remain poorly understood. Objective: This study explored associations between short-term exposures to PM with a diameter < 2.5 μm (PM2.5 ) and ozone with plasma metabolite concentrations. Methods and results: We used cross-sectional data from a cardiac catheterization cohort at Duke University, North Carolina (NC), USA, accumulated between 2001 and 2007. Amino acids, acylcarnitines, ketones and total non-esterified fatty acid plasma concentrations were determined in fasting samples. Daily concentrations of PM2.5 and ozone were obtained from a Bayesian space-time hierarchical model, matched to each patient's residential address. Ten metabolites were selected for the analysis based on quality criteria and cluster analysis. Associations between metabolites and PM2.5 or ozone were analyzed using linear regression models adjusting for long-term trend and seasonality, calendar effects, meteorological parameters, and participant characteristics. We found delayed associations between PM2.5 or ozone and changes in metabolite levels of the glycine-ornithine-arginine metabolic axis and incomplete fatty acid oxidation associated with mitochondrial dysfunction. The strongest association was seen for an increase of 8.1 μg/m 3 in PM2.5 with a lag of one day and decreased mean glycine concentrations (− 2.5% [95% confidence interval: − 3.8%; − 1.2%]). Conclusions: Short-term exposures to ambient PM2.5 and ozone is associated with changes in plasma concentrations of metabolites in a cohort of cardiac catheterization patients. Our findings might help to understand the link between air pollution and cardiovascular disease. Highlights: We explored associations between short-term exposures to PM2.5 and ozone with plasma metabolite concentrations PM2.5 and ozone were associated with changes in plasma metabolite levels Strongest association was seen for PM2.5 with a lag of one day and decreased mean glycine concentrations Our findings might help to understand the link between air pollution and cardiovascular disease